2009
DOI: 10.1007/s11060-009-9927-z
|View full text |Cite
|
Sign up to set email alerts
|

From childhood to adulthood: long-term outcome of medulloblastoma patients. The Institut Curie experience (1980–2000)

Abstract: Medulloblastoma patients treated at the Institute Curie between 1980 and 2000 were reviewed. Only patients whose primary treatment included craniospinal radiation were considered. Surviving patients were identified and evaluated by means of self-report questionnaires using the Health Utility Index (HUI). Psychosocial functioning, employment, and other health-related indicators were recorded. Seventy-three patients were treated during the study period. At a median follow-up from diagnosis of 14.4 years, 49 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
85
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 43 publications
2
85
0
6
Order By: Relevance
“…1,2 In those who survive this disease, the tumor and its treatment continue to cause effects into adulthood: 55% of survivors require endocrine-replacement therapy, and 78% have residual neurologic deficits post-treatment. 3 Recently reported overall survival rates for both children and adults are in the 60th and 70th percentiles, a significant increase from the 29% 5-year overall survival rate reported in earlier periods. 2,[4][5][6][7][8][9][10] Studies have demonstrated that medulloblastomas in adults and children are histologically and genetically different diseases.…”
Section: Introductionmentioning
confidence: 89%
“…1,2 In those who survive this disease, the tumor and its treatment continue to cause effects into adulthood: 55% of survivors require endocrine-replacement therapy, and 78% have residual neurologic deficits post-treatment. 3 Recently reported overall survival rates for both children and adults are in the 60th and 70th percentiles, a significant increase from the 29% 5-year overall survival rate reported in earlier periods. 2,[4][5][6][7][8][9][10] Studies have demonstrated that medulloblastomas in adults and children are histologically and genetically different diseases.…”
Section: Introductionmentioning
confidence: 89%
“…4 However, effective treatment options for high-risk patients with poor prognosis tumors are limited, and current therapies lack target specificity and are associated with significant neurocognitive sequelae and psychosocial deficits. 5,6 Tumor recurrence following conventional treatment remains a significant problem and the majority of patients with relapsed medulloblastoma succumb to the disease. 7 Other high grade tumors including glioblastoma, are rarer in children and adolescents (<3.0% of CNS tumors).…”
Section: N-o-d-16-00611r1mentioning
confidence: 99%
“…Medulloblastoma (MB), the most common primary malignant brain tumor of the central nervous system (CNS) during childhood 1-3 , carries long-term implications for patients' survivorship, such as neurological and cognitive deficits 4,5 , auditory and endocrine impairments 6,7 , and the perception of reduced healthrelated quality of life (HRQoL) 8 . Increased survival rates of patients with MB have led to the recognition of the importance of comprehensive assessments aimed at providing a more complete description of survivors' quality of survival (QoS) across several domains of functioning including an individual's perception of his or her cognitive performance, health status, behavior, and HRQoL.…”
Section: Introductionmentioning
confidence: 99%